2020
DOI: 10.1002/iub.2298
|View full text |Cite
|
Sign up to set email alerts
|

The halogenation of natural flavonoids, baicalein and chrysin, enhances their affinity to human protein kinase CK2

Abstract: A series of halogenated derivatives of natural flavonoids: baicalein and chrysin were designed and investigated as possible ligands for the catalytic subunit of tumor-associated human kinase CK2. Thermal shift assay method, in silico modeling, and high-performance liquid chromatography-derived hydrophobicity together with IC 50 values determined in biochemical assay were used to explain the ligand affinity to the catalytic subunit of human protein kinase CK2. Obtained results revealed that substitution of baic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 53 publications
(59 reference statements)
0
11
0
Order By: Relevance
“…Flavanones (e.g., hesperetin), flavanol (e.g., quercetin), , and flavone (e.g., baicalein) exhibit antiviral activities. Interestingly, a recent study has reported SARS-CoV-2 inhibition by baicalein (IC 50 0.94 ± 0.20 μM) and its cocrystallized structure with 3CL pro 10 . Apart from the 3CL pro in SARS-CoV-2, halogenated modification of the baicalein scaffold by halogen atoms bonding to carbon (C–X) of an aromatic ring could improve bioactivity. , Brominated baicalein (8-bromobaicalein) has shown the greatest inhibitory effect against the breast cancer cell line MCF-7 (IC 50 10 ± 3 μM) by blocking the human protein kinase CK2 . Typically, the halogen atom on the aryl halide shows an anisotropic charge distribution that can form a halogen interaction (XB).…”
Section: Introductionmentioning
confidence: 99%
“…Flavanones (e.g., hesperetin), flavanol (e.g., quercetin), , and flavone (e.g., baicalein) exhibit antiviral activities. Interestingly, a recent study has reported SARS-CoV-2 inhibition by baicalein (IC 50 0.94 ± 0.20 μM) and its cocrystallized structure with 3CL pro 10 . Apart from the 3CL pro in SARS-CoV-2, halogenated modification of the baicalein scaffold by halogen atoms bonding to carbon (C–X) of an aromatic ring could improve bioactivity. , Brominated baicalein (8-bromobaicalein) has shown the greatest inhibitory effect against the breast cancer cell line MCF-7 (IC 50 10 ± 3 μM) by blocking the human protein kinase CK2 . Typically, the halogen atom on the aryl halide shows an anisotropic charge distribution that can form a halogen interaction (XB).…”
Section: Introductionmentioning
confidence: 99%
“…Binding affinities of the newly synthesized compounds towards hCK2α were assessed with the low-volume differential scanning fluorimetry (nanoDSF). The shift of the temperature of thermal denaturation in the presence of 10-fold excess of a particular ligand relative to the apo form of hCK2α (ΔT m ) can be used as a semi-qualitative measure of the binding affinity [ 35 ] or inhibitory activity [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the most recent research, it was shown that substitution of chrysin with chlorine increases the binding affinity to human protein kinase hCK2α, which is a therapeutic target for new inhibitors used in the treatment of cancer due to the strong correlation between malignancy and abnormally high activity of this protein in cancer cells. It was observed that 8-chlorochrysin (Figure 4) had stronger binding activity to hCK2α than the reference CK2 inhibitor, 4,5,6,7-tetrabromo-1H-benzotriazole [59]. Moreover, chrysin and its porphyrin derivatives can be used in the non-invasive photodynamic therapy of human gastric cancer cells (MGC-803) and human cervical cancer cells (HeLa) [60].…”
Section: Biological Activity 41 Anticancer Activity Of Chrysin and Its Derivativesmentioning
confidence: 99%